2008
DOI: 10.1089/ten.tea.2007.0245
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Crosslinking Elastin-Like Polypeptide Gels for Application to Articular Cartilage Repair in a Goat Osteochondral Defect Model

Abstract: The objective of this study was to evaluate an injectable, in situ crosslinkable elastin-like polypeptide (ELP) gel for application to cartilage matrix repair in critically sized defects in goat knees. One cylindrical, osteochondral defect in each of seven animals was filled with an aqueous solution of ELP and a biocompatible, chemical crosslinker, while the contralateral defect remained unfilled and served as an internal control. Joints were sacrificed at 3 (n = 3) or 6 (n = 4) months for MRI, histological, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
62
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(66 citation statements)
references
References 41 publications
4
62
0
Order By: Relevance
“…These hydrogels degraded rapidly. (Nettles et al, 2008) Table 3. In-situ forming hydrogels for in vivo cartilage regeneration…”
Section: Rabbit Osteochondral Defectmentioning
confidence: 99%
“…These hydrogels degraded rapidly. (Nettles et al, 2008) Table 3. In-situ forming hydrogels for in vivo cartilage regeneration…”
Section: Rabbit Osteochondral Defectmentioning
confidence: 99%
“…A biocompatible, trifunctional, amine-reactive crosslinker, b-[tris(hydroxymethyl) phosphino] propionic acid (betaine) (THPP; Pierce Biotechnology, Rockford, IL), 20,48,57 was dissolved in 200 mL of 25 mM HEPES-buffered saline to a final concentration of 250 mg=mL. Aliquots of this solution were stored at À808C until further use.…”
Section: Crosslinker Preparationmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14] Scaffolds have included those that are prefabricated ex situ 4,9,[15][16][17] or those that may be injected, [18][19][20] and they have been formed from a variety of natural and synthetic materials. Several studies have demonstrated that material formulation parameters affect the mechanical properties of these scaffolds as well as their ability to support chondrogenesis by encapsulated or seeded cells.…”
Section: Introductionmentioning
confidence: 99%
“…Structural proteins like elastin, collagen and silk often contain repeating peptide motifs, and are therefore translated from repeating DNA sequences 7 . This has sparked an interest in engineered 'proteinpolymers,' developed with similar motifs from repeating DNA to optimize structural properties 8,9 .…”
mentioning
confidence: 99%